Clean energy consumption, economic growth, and environmental sustainability: What is the role of economic policy uncertainty?. (January 2022) - Xue, Chaokai; Shahbaz, Muhammad; Ahmed, Zahoor; Ahmad, Mahmood; Sinha, Avik
Abstract: Undoubtedly, energy is indispensable to attain economic development; however, it also generates CO2 emissions, which are the dominant contributor to environmental deterioration and climate change. In this regard, clean energy can help to achieve both sustainable development and environmental sustainability since it comprises non-carbohydrate energy sources that do not or seldom generate emissions. Against this backdrop, this work considers economic policy uncertainty (EPU) and probes the impact of clean energy consumption on CO2 emissions in the third largest European economy France from 1987 to 2019 controlling urbanization and economic growth. Using the STIRPAT framework, the study employed the novel Augmented ARDL method that overcomes the limitations of the ARDL methods. The outcomes disclosed strong evidence of cointegration. The long-run analysis revealed that clean energy consumption does not contribute to emissions reduction in the long-run. However, EPU poses a threat to environmental sustainability by augmenting emissions levels. Economic growth boosts CO2 emissions, while urbanization is conducive to environmental quality supporting ecological modernization theory. The study detected causality from EPU to economic growth and emissions. Finally, based on the study outcomes, a policy framework is suggested to address the objectives of Sustainable Development Goal (SDG) 7 and 13. Highlights: Estimated effects of clean energy and EPU on emissions using augmented ARDL method. Findings indicate cointegration in the model. EPU increases CO2 emissions. Economic growth augments emissions while urbanization reduces emissions. Clean energy consumption does not significantly contribute to CO2 reduction.